Pengaruh ROA dan Besaran Dividen terhadap Harga Saham bagi Calon Investor pada Bank BUMN tahun 2008-2010 - ., Anasrul; Rahim, Anwar; Ishardyatmo, Handono (Jurnal Manajemen, 2015)
This study aimed to determine the Return On Asset (ROA), Cash Dividend, and the effect of Return on Assets (ROA) and Cash Dividend on Stock Price. According to this study, Return On Asset (ROA) effect to positive stock price +1.887 and significant with probability of 0.0032 < 0.05. Cash Dividend showed that the effect to the low negative stock prices -0.067, but not significant with probability of 0.7120 > 0.05. The results showed that there was no deviation assumption of normality. It means that the available data were qualified to use the multiple linear regression models. The results of analysis showed that data of ROA and cash dividend simultaneous have a significant influence on stock price. However, the prospective investors who will invest should understand the analysis of the stock such as fundamental and technical so that can provide significant benefits and avoid greater risks.